(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2025)
Bread wheat (Triticum aestivum L.) is the most valuable crop in Ethiopia. The low yield of existing varieties has been partly attributed to high wheat rust pressure and recurrent drought in the country. Field experiments were carried out in Halaba, Inseno, and Lanfero, South Ethiopia, during 2019, 2020, and 2022 cropping seasons, with the objective to obtain rust-resistant and high-yielding genotypes for low moisture stress areas. Under regional variety trials of 2019 and 2020, fifteen advanced lines and a local check variety, Ogolcho (released in 2011), were grown using four replications in a randomized complete block design. Plant height was 83.25, 87.73 and 78, 68 cm; yield was 3.18, 3.72 and 4.43 tons ha-1; and 1000-seed weight was 38.10, 33.07 and 39.54 g, respectively, for Halaba, Inseno and Lanfero. Plant height was 80.86, 81.61, 80.07, and 85.84 cm; yield was 4.09,4.23, 4.16, and 3.56 tons ha-1; and 1000-seed weight was 38.41, 35.46, 39,58, and 37.57 g, for the high yielding genotypes ETBW9131, ETBW9152, ETBW9077, and the check variety Ogolcho, respectively. Under variety verification trials of 2022, genotype ETBW9131, a local check variety, Ogolcho and a standard check variety, Biftu (released in 2022), were grown. The yield was 4.58, 3.35, and 2.96 tons ha-1 for ETBW9131, Biftu, and Ogolcho, respectively. For its high yield, moderate susceptibility to stem rust and moderate resistance to yellow rust, ETBW9131 has been released and registered by the variety name ‘Kulito’ for cultivation in low moisture stress areas of Halaba, Inseno, Lanfero, and other areas with similar agro-ecologies. Int. J. Agril. Res. Innov. Tech. 15(1): 109-114, June 2025